2021
DOI: 10.1038/s41545-020-00091-1
|View full text |Cite
|
Sign up to set email alerts
|

Design, performance, and demand for a novel in-line chlorine doser to increase safe water access

Abstract: Financially sustainable strategies are needed to increase access to safe drinking water in low-income settings. We designed a novel in-line chlorine doser that employs the Venturi principle to automatically add liquid chlorine at the point of water collection (tap outflows). The Venturi does not require electricity or moving parts, and users do not have to change the way they typically collect water. We field-tested the Venturi and assessed its technical performance and sales viability at water kiosks in Kisum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Although WHO guidelines for residual in piped water systems recommend 0.2–0.5 mg/L FCR as adequate for disinfection, 49 some studies defined adequate chlorine delivery as any amount of measurable free chlorine above the limit of detection 17 , 32 , 38 , 40 , 44 , 45 or used their own range of desired doses on the basis of other standards. 21 , 33 , 34 , 42 , 46 , 48 Dosing consistency was reported as the percentage of samples with chlorine concentrations within the study’s indicated range ( Table 2 ).…”
Section: Implementation and Evaluation Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…Although WHO guidelines for residual in piped water systems recommend 0.2–0.5 mg/L FCR as adequate for disinfection, 49 some studies defined adequate chlorine delivery as any amount of measurable free chlorine above the limit of detection 17 , 32 , 38 , 40 , 44 , 45 or used their own range of desired doses on the basis of other standards. 21 , 33 , 34 , 42 , 46 , 48 Dosing consistency was reported as the percentage of samples with chlorine concentrations within the study’s indicated range ( Table 2 ).…”
Section: Implementation and Evaluation Studiesmentioning
confidence: 99%
“… 32 , 33 , 48 Stanford-MSR Venturi relies on the Venturi effect to pull chlorine into running water flowing through the chlorinator. 48 Zimba is a batch doser that relies on water reaching a specified level to trigger the addition of a fixed amount of chlorine. 33 Nirapad Pani, which was designed for use with handpumps (but not commercialized), uses suction generated by operating the handpump to pull liquid chlorine into the water.…”
Section: Implementation and Evaluation Studiesmentioning
confidence: 99%
See 3 more Smart Citations